93 Sacituzumab govitecan in uterine and ovarian carcinosarcomas. (18th September 2019) - Lopez, S; Perrone, E; Zeybek, B; Bellone, S; Manzano, A; Zammataro, L; Han, C; Altwerger, G; Angioli, R; Santin, A
Abstract : Objectives: Carcinosarcomas (CS) are highly aggressive gynecologic malignancies containing both carcinomatous and sarcomatous elements. Sacituzumab govitecan (SG) is a novel antibody-drug conjugate (ADC) targeting trophoblast antigen 2 (Trop-2), a cell surface glycoprotein highly expressed in many epithelial tumors, to deliver SN-38, the active metabolite of irinotecan. This study aimed to evaluate the efficacy of SG in primary CS cell lines and xenografts. Methods: Trop-2 expression in primary tumor cell lines and cell viability after exposure to SG, non-targeting control ADC (h679-CL2A-SN-38), and naked parental antibody hRS7 IgG were evaluated using flow-cytometry-based-assays. Antibody-dependent-cell-cytotoxicity (ADCC) against Trop-2+ and Trop-2- CS cell lines was evaluated in vitro using 4-h Chromium-release-assays. In vivo activity of SG was tested against Trop-2+ CS xenografts. Results: High expression of Trop-2 was detected in 55, 5% (5 of 9) of primary CS cell lines. Primary tumors overexpressing Trop-2 were significantly more sensitive to SG when compared to control ADC (p<0.05). Both SG and parental hRS7 mediated high level of ADCC against Trop2+ CS cell lines while no cytotoxicity was detected against Trop-2 negative tumors. Importantly, SG also induced bystander killing of Trop-2 negative tumors. In vivo experiments with SG demonstrated significantly greater antitumor effects and increased survival compared to control ADC (p<0.05). SG therapy was well tolerated by the animals. Conclusions: SG demonstrated remarkable antitumor activity against biologically aggressive CS overexpressing Trop-2 and due to its hydrolizable linker may cause a significant bystander killing effect in CS with heterogenous TROP-2 expression. Clinical trials are warranted.